The literature of Romanian pneumophthisiology at the beginning of twentieth century - Daniela Mihăilescu (Romanian Medical Journal, 2020)
This article presents doctoral papers in medicine and surgery from the early twentieth century, within the Faculty of Medicine Bucharest and the Bucharest Military Medical Institute, supported by interns or former inmates of Bucharest Hospitals, Philanthropy Hospital, Military Hospital "Regina Elisabeta” or the Military Medical Institute. As Presidents and members of the commissions supporting these Doctorates were important personalities of the medical world at that time: Prof. Dr. N. Măldărescu, Prof. Dr. G. Stoicescu, Prof. Dr. I. Cantacuzino, Prof. Dr. Gr. Romniceanu, Prof. Dr. Victor Babeş, Prof. Dr. C. Parhon, Prof. Dr. G. Proca, Prof. Dr. G. Marinescu, Prof. Dr. C. Severeanu, Prof. Dr. N. Kalinderu, Prof. Dr. N.C. Thomescu, Prof. Dr. Paul Petrini and others. The paper aims to present the results of studies of high scientific standing, well located in the context of contemporary studies, moments of reference in the specialty. These studies represent an important step in the evolution and development of Romanian pneumophthisiology